Study on inflammatory conditions of uterus in Buffalo (Bubalus bubalis) - SAXENA, GARIMA; RANI, SUNITA; PUROHIT, G N (The Indian Journal of Animal Reproduction, 2023)
In the present study 266 genitalia of buffalo were examined, out of which 52 genitalia revealed inflammatory conditionsin uterus and they were classified into endometritis (30 cases) and metritis (22 cases). Endometritis was further subdivided intoacute ( I case), subacute (5 cases) and chronic endometritis (24 cases). Gross and histopathological features are described inpresent paper.